Glutaminase inhibitory activity of umbelliferone isolated from kabosu (Citrus sphaerocarpa Hort. ex Tanaka). Issue 2 (17th January 2022) - Shimada, Atsumi; Ueno, Hiroshi; Inagaki, Masanori; Yoshimitsu, Hitoshi
Abstract: Kabosu ( Citrus sphaerocarpa Hort. ex Tanaka) fruits have pleasant and fresh odors and have been used as raw materials for vinegar, seasonings, jams, marmalades and juices in Japan. The n -butanol extracts from kabosu fruits were prepared and a component in the extract was purified by column chromatography and HPLC to afford compounds 1 -3 . Three compounds, 5-(hydroxymethyl)-2-furaldehyde (1 ), umbelliferone (2 ) and oxypeucedanin hydrate (3 ), have been isolated from kabosu, and the structures of compounds 1 -3 were elucidated by 1 D and 2 D NMR as well as EI-MS. Compound 2 exhibited potent glutaminase inhibitory activity with an IC50 value of 1.33 mM. This is the first report on glutaminase inhibitory activity of 2 and the isolation of three compounds 1 -3 from kabosu fruits. Abstract : UF0001